STUDY OF THE MICROFLORA AND PH OF THE SKIN ENVIRONMENT IN PATIENTS WITH ZOOANTHROPONOTIC TRICHOPHYTOSIS OF THE PUBIC REGION (World Bulletin of Public Health, 2024)
The article describes the Study of the microflora and pH of the skin environment in patients with zooanthroponotic trichophytosis.
Keywords: Zoo anthroponotic; trichophytes and features; microbiology